The role of soils in social development of society - Гавриш, Наталія Степанівна; Гавриш, Н.С.; Гавриш, Наталия Степановна; Havrysh, Natalia S.; Позняк, Степан Павлович; Позняк, С. П.; Pozniak, Stepan P. (Kyiv : Institute of Geography Ukraine NAS, 2019)
The article contains the author’s reflections on the formation and substantiation of many aspects in soil concerning its connections with social sciences. Arguments about the exceptional importance of soil resources modern world and the importance of scientific research in soil science, which can become an important instrument solving social problems, are found. It is shown that soil resources, being the basis of agricultural development, ‘long-term’ capital through which different nations exist and develop, in order to maintain the population normal conditions and to its improving, it is important to use this global resource wisely. The attitude of people to the recognized as fundamental for nations sustainable development and, moreover, the life expectancy of a civilization depend on the people attitude to soils. In order to maintain collective well-being of people, a long-term interest society in soil protection needs to be reoriented – this should become a priority task for our civilization. The current state of soils can serve not only as a characteristic of the development of society, but also a criterion for assessing the activity of power and social stability of the country. Taking into account the predominantly unique composition of the soil covers of the country in the productive and ecological aspects, the purpose of the land reform was to become a full-fledged landowner, who would not only receive high yields, but also take care of the soil fertility. In order the soil perform a social function, it is necessary to develop organizational, technological, technical, educational, aesthetic and educational measures, soil-saving innovative technologies, conservation tools, obligatory observance of technologies, training of qualified specialists in soil science, active land and legal policy of the state.

Стаття висвітлює виняткову важливість ґрунтів у сучасному світі та значущість наукових досліджень з ґрунтознавства, які можуть стати важливим засобам розв’язання соціальних проблем. Показано, що ґрунтові ресурси, як основа сільськогосподарського розвитку, є тим «довготерміновим» капіталом, за допомогою якого існують і розвиваються різні нації. Для підтримання колективного благополуччя людей потрібна переорієнтація на довготермінову зацікавленість суспільства в охороні ґрунтів. Сучасний стан ґрунтів може слугувати не лише характеристикою розвиненості суспільства, а й критерієм оцінювання діяльності влади та соціальної стабільності країни. Для того, щоб ґрунт виконував соціальну функцію, необхідно впроваджувати ґрунтозбережувальні інноваційні технології, ощадливі знаряддя, проводити активну земельно-правову політику держави, організаційні, освітянські, естетичні та виховні заходи.
Pozniak S. The role of soils in social development of society / S. Pozniak, N. Havrysh // Ukrainian Geographical Journal. - Kyiv : Institute of Geography Ukraine NAS, 2019(2). - Р. 57-61.
Keywords: soil; soil resources; soil conservation technologies; pedology; ґрунт; ґрунтові ресурси; ґрунтозбережувальні технології; ґрунтознавство; Research Subject Categories::FORESTRY, AGRICULTURAL SCIENCES and LANDSCAPE PLANNING::Soil science